Collisionless Shocks as a Diagnostic Tool for Understanding Energetic Particle Transport in Space Plasmas - Zimbardo, Gaetano; Prete, Giuseppe; Perri, Silvia (Frontiers in Astronomy and Space Sciences, 2020)
We study the transport of energetic particles accelerated at three different shock events observed in the solar wind by the ACE spacecraft. We consider particle propagation for a quasi-parallel, an oblique, and a quasi-perpendicular shock. The transport regime is deduced from the shape of the energetic particle profiles upstream of the shock, and for these events the profiles are well fitted by power-laws with slope $β$. This corresponds to a superdiffusive transport with the anomalous diffusion exponent $α = 2 - β$ when $β < 1$, and to normal diffusion when $β\ge1$. We checked the resonant turbulence level upstream of the shocks, finding that this is statistically constant, so that the transport regime is not expected to change with the shock distance. For the three shocks under study, particle transport upstream of the shock is mostly superdiffusive, although the superdiffusive character appears to diminish with the increase of the shock normal angle $θ_{\rm Bn}$. We discuss possible interpretations of these results.